Analysis of factors influencing contact in the 686 Program for patients with a first-time diagnosis of severe mental disorders in Hainan Province from 2018 to 2022 - Xin Zuo; Jianhe Hong; Di Liang; Wenting Cao; Qiqing Liang; Yumei Liu (BMC Psychiatry)
Abstract Background The 686 Program in China primarily aims to provide certain health and policy services to individuals with severe mental disorders within the community. As of 2020, a total of 6.43 million patients were registered nationwide under this program. However, there remains a disparity between the actual number of patients covered by the program and the total number of individuals with mental disorders. Factors influencing the engagement in 686 Program among individuals with severe mental disorders remain underexplored in current research.This study aims to understand the barriers and facilitators to program contact, offers implications for the development of targeted interventions for people with severe mental disorders, enabling the creation of more tailored and impactful strategies to enhance the 686 Program’s effectiveness and reach. Objective We aimed to explore the influencing factors associated with the registration and management of the 686 Program in a clinical sample of inpatients with severe mental disorders. Method This study employed a cross-sectional study design. Demographic information, behavioral characteristics, and clinical information of inpatients firstly diagnosed with severe mental disorders from 2018 to 2022 were retrieved from the Hainan Provincial Anning Hospital information system, subsequently, registration and management data were matched using resident ID numbers within the 686 Program information system to effectively align independent and dependent variables. Binary logistic regression analysis was utilized to investigate the factors influencing the registration and management of the 686 Program among the first confirmed patients with severe mental disorders. Results Between 2018 and 2022, Hainan Provincial Anning Hospital had 3,008 individuals who were first diagnosed with severe mental disorders. Among them, 1135 (37.73%) did not register for 686 Program, and 1873 (62.67%) had registered the 686 Program, of which 82 (4.38%) were unwilling to accept management. Multivariable analysis revealed that older age(OR = 1.010, 95% CI: 1.002–1.019), local (OR = 1.356, 95% CI: 1.014–1.814), longer disease duration (OR = 1.031, 95% CI: 1.015–1.047), total number of hospitalizations (from initial diagnosis onward) > 1 time (OR = 1.362, 95% CI: 1.135–1.635; OR = 3.287, 95% CI: 2.579–4.189) and smoking(OR = 1.383, 95% CI: 1.081–1.769) were associated with a higher likelihood of registering for the 686 Program. Conversely, being ethnic minorities (OR = 0.707, 95% CI: 0.500-0.998), individuals with a middle school education and above(OR = 0.477, 95% CI: 0.276–0.823; OR = 0.357, 95% CI: 0.204–0.623), and those diagnosed with bipolar disorder (OR = 0.459, 95% CI: 0.357–0.590) were less inclined to register for the 686 Program. Furthermore, local resident status (OR = 2.455, 95%CI: 1.212–4.970) and being married (OR = 1.909, 95%CI:1.023–3.564) were associated with a higher likelihood of receiving community health management, while older age (OR = 0.954, 95%CI:0.924–0.986) was associated with a decreased likelihood of accepting management. Conclusion We found that older patients, longer disease duration, total number of hospitalizations (from initial diagnosis onward) > 1 time, local resident status, and smokers are more inclined to register for the 686 Program. Ethnic minorities, individuals with a junior high school education or above, and those diagnosed with bipolar affective disorder are more hesitant to register for the 686 Program, additionally, patients who are local residents and married are more likely to receive community health management, older patients are more reluctant to accept community health management. In the future, relevant departments should take targeted measures, especially focusing on promotional efforts for ethnic minorities, individuals with a junior high school education or above, and those diagnosed with bipolar affective disorder to enhance the accessibility and popularity of the 686 Program. Furthermore, it is essential to investigate the reasons behind the reluctance of older patients to accept community health management services, in order to improve the effectiveness of the 686 Program for this demographic.